National Well-being Policy and a Weighted Approach to Human Feelings - Gus O'Donnell; Andrew J. Oswald (Institute for the Study of Labor (IZA), 2015)
Governments are becoming interested in the concept of human well-being and how truly to assess it. As an alternative to traditional economic measures, some nations have begun to collect information on citizens' happiness, life satisfaction, and other psychological scores. Yet how could such data actually be used? This paper is a cautious attempt to contribute to thinking on that question. It suggests a possible weighting method to calculate first-order changes in society's well-being, discusses some of the potential principles of democratic 'well-being policy', and (as an illustrative example) reports data on how sub-samples of citizens believe feelings might be weighted.
Keywords: I31; I38; Z18; 330; life satisfaction; anxiety; happiness; national well-being; mental health